Sepsis due to Weeksella virosa in wounds made by animal bite. A case report. - Elio Jesús Núñez Tamayo; Susana Chamero Melgarejo; Nancy Ramírez Martínez (Medisur)
This paper contains a case report of acute sepsis due to Weeksella virosa, a Gram negative micro-organism non fermentative of positive oxidase carbohidrates in a healthy patient aged 31 who was assisted at the service of microbiology of the ¨Dr. Gustavo Aldereguía Lima¨ Hospital in March 2003. The clinical symptoms were fever, pain, limited movements, erythema and sensation of warm. A diagnosis of reticular lymphangitis was done and Weeksella virosa was isolated by a conventional diagnosis. Tests for antimicrobial susceptibility showed sensitivity to tetracycline, aztreonam, ceftriazone and resistance to imipenem. Treatment was applied with tetracycline 1 gr. Daily for 7 days. The clinical picture improved with total regression of symptom.